Emerging Developments in Human Induced Pluripotent Stem Cell-Derived Microglia: Implications for Modelling Psychiatric Disorders With a Neurodevelopmental Origin - Hanger, Bjørn; Couch, Amalie; Rajendran, Lawrence; Srivastava, Deepak P.; Vernon, Anthony C. (Frontiers in Psychiatry, 2020)
Microglia, the resident tissue macrophages of the brain, are increasingly implicated in the pathophysiology of psychiatric disorders with a putative neurodevelopmental origin, such as schizophrenia. We currently lack however, a validated human in vitro system to study microglia biology or microglia-neuron interactions in this context. Primarily, this gap reflects the lack of access to human primary tissue during early developmental stages. In this review, we advance the suggestion that microglia derived from human induced pluripotent stem cells (hiPSC) may fill this gap. In doing so, we first briefly describe microglia, including their ontogeny and heterogeneity and consider their roles in brain development. We then provide an evaluation of the current state of the art in terms of differentiating microglia from hiPSCs and consider their potential for the study of neurodevelopmental psychiatric disorders. We find the majority of protocols for hiPSC-derived microglia generate cells characteristically similar to foetal stage microglia when exposed to neuronal environment-like cues. Such models clearly have the potential to provide a robust and relevant model for the study of microglia in the context of neurodevelopmental psychiatric disorders. Key questions however remain particularly concerning mimicking “authentic” microglia ontogeny in the differentiation protocol as well as how to confirm and validate a “true” microglia phenotype. Questions over the similarity of hiPSC microglia to human primary microglia also remain to be addressed in order to develop a robust and translatable hiPSC-microglia model to advance this field.